Karakter morfologi bakteri dari daun sehat dan bergejala sakit Lidah Buaya (Aloe vera var. barbadensis) - Ahmad Mulyadi, Yoas Leo G.M.T, Siti Khotimah, (Jurnal Protobiont, 2014)
Plant diseases caused by bacteria will decrease the production of Aloe vera var. barbadensis. Bacteria that infect the leaves of Aloe vera can be recognized by symptoms on plants that the leaves become soft rot and dry rot. This study aims to determine the density of bacterial colonies, colony morphology and the morphology of bacterial cells of healthy leaves and leaves of symptomatic illness. The method used is the Total Plate Count (TPC). The results showed that most bacteria found in the leaves of symptomatic illness that 7 isolates soft rot and bacterial colony density that is 237 X 10-7cfu/g. Bacteria were recovered from healthy and symptomatic illness leaves are 16 isolates, that showed characteristic colony circumference shape, curved, long, flat elevation, convex, flat, flat edges, uneven and curved, while the morphology of bacterial cells are coccus, bacillus and spirilum.